2015
DOI: 10.1038/ejcn.2015.147
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cholestasis in patients on parenteral nutrition: the influence of restoring bowel continuity after mesenteric infarction

Abstract: The prevalence of CC is 29% for patients with a short bowel receiving PN following a mesenteric infarction. CC resolves in 53% after continuity is restored, and this is most likely due to stopping or reducing the PN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Of note, it has been shown that phytosterols, major constituents of soybean oil, promote cholestatic liver disease, highlighting the need to minimize use of soybean oil-based lipid emulsions to prevent cholestatic liver injury (24,25). Although liver failure due to IFALD remains the main indication for intestine or combined liver-intestine transplantation, more recent studies showed declines in the prevalence of chronic cholestatic liver injury (20-30%) relative to the 50% prevalence reported in an initial study in 2000 (5,8,9). In the large cohort studied here, we found a slightly lower prevalence of 17%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, it has been shown that phytosterols, major constituents of soybean oil, promote cholestatic liver disease, highlighting the need to minimize use of soybean oil-based lipid emulsions to prevent cholestatic liver injury (24,25). Although liver failure due to IFALD remains the main indication for intestine or combined liver-intestine transplantation, more recent studies showed declines in the prevalence of chronic cholestatic liver injury (20-30%) relative to the 50% prevalence reported in an initial study in 2000 (5,8,9). In the large cohort studied here, we found a slightly lower prevalence of 17%.…”
Section: Discussionmentioning
confidence: 99%
“…Between 24% and 65% of CIF patients develop liver injury (e.g., steatosis, cholestasis, or fibrosis), collectively known as intestinal failure-associated liver disease (IFALD) (5)(6)(7)(8)(9). Ultimately, IFALD may progress to liver failure, which is accompanied by higher rates of referral for intestinal or multivisceral transplantation (ITx) and home parenteral nutrition (HPN)-related mortality (10).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, surgical strategies that restore gastro‐intestinal continuity should be considered at an early stage of a patient's CIF care pathway. Adaba et al demonstrated that eight of 15 (53%) home PN‐dependent adults with chronic cholestasis had a return of LFTs to the normal range within one year of restoration of bowel continuity . Where restoration of continuity cannot be achieved, intestinal lengthening procedures offer a viable alternative to both adults and children .…”
Section: Managementmentioning
confidence: 99%
“…Adaba et al demonstrated that eight of 15 (53%) home PN-dependent adults with chronic cholestasis had a return of LFTs to the normal range within one year of restoration of bowel continuity. 66 Where restoration of continuity cannot be achieved, intestinal lengthening procedures offer a viable alternative to both adults 95 and children. [96][97][98] Yannam et alreported successful outcomes in 20 adult patients with CIF undergoing intestinal lengthening with a 90% survival rate and 10 patients achieving complete weaning of PN with restoration of enteral autonomy.…”
Section: Absorptive Capacitymentioning
confidence: 99%
“…The early restoration of intestinal passage is more advantageous than intestinal ostomy. In the case of active nutritional support to a patient with a stoma, parenteral nutrition increases the risk of cholestasis and liver failure; only restoration of the enteral digestion leads to restoration of liver function [10]. In patients with an ultrashort small intestine remaining after emergency resection, restoration of the intestinal passage by imposing an anastomosis between the jejunum and the colon reduces the risk of recurrent ischemic damage and leads to the cancellation of parenteral nutrition in 35-50% of cases within a year [11].…”
Section: Introductionmentioning
confidence: 99%